2019
DOI: 10.3324/haematol.2018.214320
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric ferrochelatase bridges ABCB7 and ABCB10 homodimers in an architecturally defined molecular complex required for heme biosynthesis

Abstract: Loss-of-function mutations in the ATP-binding cassette (ABC) transporter of the inner mitochondrial membrane, ABCB7, cause X-linked sideroblastic anemia with ataxia, a phenotype that remains largely unexplained by the proposed role of ABCB7 in exporting a special sulfur species for use in cytosolic iron-sulfur (Fe-S) cluster biogenesis. Here, we generated inducible ABCB7-knockdown cell lines to examine the time-dependent consequences of loss of ABCB7. We found that knockdown of ABCB7 led to significant loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 50 publications
2
51
0
Order By: Relevance
“…In addition, α-ketoglutarate dehydrogenase (KDH) and succinyl-CoA synthase (SUCLA2), which synthesize the heme precursor succinyl-CoA, and TMEM14C, a porphyrinogen transporter [39,82], were also observed in the complex. Independent studies have also shown mitoferrin, a mitochondrial iron importer [84], as well as two ATP binding cassette proteins, ABCB7 [85,86] and ABCB10 [84,86] are protein partners of FECH. These results would suggest that substrate channeling and assembly of the heme metabolon complex may be a key regulatory node for heme synthesis.…”
Section: Ferrochelatasementioning
confidence: 99%
“…In addition, α-ketoglutarate dehydrogenase (KDH) and succinyl-CoA synthase (SUCLA2), which synthesize the heme precursor succinyl-CoA, and TMEM14C, a porphyrinogen transporter [39,82], were also observed in the complex. Independent studies have also shown mitoferrin, a mitochondrial iron importer [84], as well as two ATP binding cassette proteins, ABCB7 [85,86] and ABCB10 [84,86] are protein partners of FECH. These results would suggest that substrate channeling and assembly of the heme metabolon complex may be a key regulatory node for heme synthesis.…”
Section: Ferrochelatasementioning
confidence: 99%
“…However, Slc25a28 mRNA was diminished under the same treatment, a response that would be in line with an iron export factor. In comparison, Abcb7 and Abcb8 (ATP binding cassette subfamily B member 7/8) are thought to have mitochondrial export functions [ 72 , 80 , 81 , 82 ] and are also important for heme biosynthesis [ 83 ]. As expected after iron depletion, Abcb7 transcript levels were halved, similar to Abcb8 ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The substrates of ABCB10 transport activity are currently undefined, but its absence was reported to reduce mitoferrin-1 protein levels, iron import into mitochondria, heme biosynthesis, and hemoglobinization, while a role in the export of ALA (5′-aminolevulinic acid) was excluded [ 182 ]. It is difficult to identify the individual substrates for each mitochondrial transporter protein, given that ABCB10, the putative iron-importer mitoferrin, the heme-synthesis factor ferrochelatase, and the ISC-exporter ABCB7 coexist in a protein complex [ 72 , 79 , 83 , 183 ] where the deletion of one member may destabilize also its interactors. Similar to ABCB10, a decrease of iron import and heme biosynthesis was also shown upon deletion of mitoferrin [ 184 , 185 ], leading to universal acceptance of mitoferrin as the main mitochondrial iron importer [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…into mitochondria, heme biosynthesis and hemoglobinization, while a role in the export of ALA was excluded [95]. It is difficult to identify the individual substrates for each mitochondrial transporter protein, given that Abcb10, the putative iron-importer mitoferrin, the heme-synthesis factor ferrochelatase, and the ISC-exporter Abcb7 coexist in a protein complex [61,62,66,96] where the deletion of one member may destabilize its interactors. Similar to Abcb10, a decreased iron import and heme biosynthesis was also shown upon deletion of mitoferrin [97,98], leading to universal acceptance of mitoferrin as main mitochondrial iron importer [99].…”
Section: Discussionmentioning
confidence: 99%
“…and Abcb8 are thought to have mitochondrial export functions [62][63][64][65] and are also important for heme biosynthesis [66]. As expected after iron depletion, Pursuing the heme-and ISC-associated pathways into the cytosol, it is relevant that the putative heme release factor Pgrmc1, as cytosolic factor in association with mitochondrial ferrochelatase, showed a more than two-fold transcriptional induction after iron depletion (DFO: 2.30-fold with p<0.0001; 22BP: 2.16-fold with p<0.0001).…”
Section: Transcriptional Analyses Of Cellular Iron Homeostasis Factormentioning
confidence: 99%